Shifts in d15N signature following the onset of exogenous feeding in fishes: Importance of combining length and age data - Liberoff, Ana Laura (2013)
The 15N isotopic change of recently emerged rainbow trout (Oncorhynchus mykiss) due to diet shift from yolk sac to exogenous feeding was evaluated in a field study. The fit of a general model including both fish length and age in days as co-variables indicates that the collection of isotope signatures could have arisen from a dilution process of a common maternally inherited signature. The results suggest that the specific 15N of individual fish at any given time along the ontogeny is determined by its growth trajectory and not by time or size alone. The results are discussed in the context of the potential bias in determining maternal origin in partially migratory salmonids through muscle isotope ratios based on fish size alone.